2017
DOI: 10.1016/j.biopsycho.2017.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Goal impact influences the evaluative component of performance monitoring: Evidence from ERPs

Abstract: Successful performance monitoring (PM) requires continuous assessment of context and action outcomes. Electrophysiological studies have reliably identified event-related potential (ERP) markers for evaluative feedback processing during PM: the Feedback-Related Negativity (FRN) and P3 components. The functional significance of FRN remains debated in the literature, with recent research suggesting that feedback's goal relevance can account for FRN (amplitude) modulation, apart from its valence or expectedness al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 86 publications
(139 reference statements)
1
17
1
Order By: Relevance
“…Relevance was understood in this study as the degree to which a stimulus was informative about the satisfaction status of pursued goals (see also Moors, 2007). Moreover, in another recent EEG study, we found evidence that goal relevance understood as impact increased the P3b during PM (Severo et al, 2017. Impact corresponded to the amount of goal satisfaction that was signaled by the feedback stimulus.…”
Section: Action Value Updating At the P3b Levelsupporting
confidence: 59%
See 4 more Smart Citations
“…Relevance was understood in this study as the degree to which a stimulus was informative about the satisfaction status of pursued goals (see also Moors, 2007). Moreover, in another recent EEG study, we found evidence that goal relevance understood as impact increased the P3b during PM (Severo et al, 2017. Impact corresponded to the amount of goal satisfaction that was signaled by the feedback stimulus.…”
Section: Action Value Updating At the P3b Levelsupporting
confidence: 59%
“…for each type of feedback separately; and (h) low-pass digital filtering of the individual average data (30 Hz). 4 In accordance with previous ERP studies focused on feedback-based PM (Aarts & Pourtois, 2012;Bismark, Hajcak, Whitworth, & Allen, 2013;Ferdinand et al, 2012;Fischer & Ullsperger, 2013;Pfabigan et al, 2011;Severo et al, 2017Severo et al, , 2018von Borries et al, 2013;Walentowska et al, 2016;Walsh & Anderson, 2012) as well as the electrophysiological properties of the current data set (see Figure 3), the FRN was defined as the mean voltage within 250-300 ms after feedback onset over frontal and frontocentral electrodes along the midline (Fz and FCz pooled together). The P3b amplitude was measured as a mean voltage between 350 and 600 ms after feedback onset at centroparietal and parietal electrodes (CPz and Pz pooled together).…”
Section: Eeg Acquisition and Erp Analysesmentioning
confidence: 75%
See 3 more Smart Citations